Evaluation of three‐dimensional porous chitosan–alginate scaffolds in rat calvarial defects for bone regeneration applications. Issue 10 (4th June 2013) - Florczyk, Stephen J.; Leung, Matthew; Li, Zhensheng; Huang, Jerry I.; Hopper, Richard A.; Zhang, Miqin
<x xml:space="preserve">Abstract</x> This study investigated the use of three‐dimensional porous chitosan–alginate (CA) scaffolds for critical size calvarial defect (diameter, 5.0 mm) repair in Sprague–Dawley rats. CA scaffolds have been used for in vitro culture of many cell types and demonstrated osteogenesis in ectopic locations in vivo, but have yet to be evaluated for functional bone tissue engineering applications. CA scaffolds demonstrated the ability to support undifferentiated mesenchymal stem cells (MSCs) in culture for 14 days in vitro and promoted spherical morphology. In vivo tests were performed using CA scaffolds and CA scaffolds with treatments including undifferentiated MSCs, bone marrow aspirate, and bone morphogenetic protein‐2 (BMP‐2) growth factor in comparison to unfilled bone defect used as a control. The samples were analyzed with MicroCT, histology, and immunohistochemical staining at 4 and 16 weeks. Partial defect closure was observed in all experimental groups at 16 weeks, with the greatest defect closure (71.56 ± 19.74%) in the animal group treated with CA scaffolds with BMP‐2 (CA + BMP‐2). The experimental samples demonstrated osteogenesis in histology and immunohistochemical staining, with the CA + BMP‐2 group, showing the greatest level of osteogenesis. Tissue engineered CA scaffolds show promise in reconstruction of critical size bone defects. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 2974–2983, 2013.